Surgical removal of dental implants displaced into the maxillary sinus - Chrcanovic Ramos Bruno; Custódio Neto Luís Antônio (Stomatološki glasnik Srbije, 2009)
The accidental displacement of roots, endodontic materials and dental implants into the maxillary sinus are relatively common complications in dental clinical practice. The purpose of this study is to present four cases of displaced dental implant into maxillary sinus, their treatment as well as the prevention of this condition. There are three different major approaches to remove materials displaced into the maxillary sinus: suction from the socket of an extracted tooth, the classical open surgery via the canine fossa and endoscopic approach. A relevant improvement of surgical techniques previous to, or in association with, the placement of implants in the posterior maxilla, has tremendously expanded the possibilities and indications for such treatments. To decrease the risk for developing side effects, it is recommended that sinus augmentation procedures should be performed before inserting implants in a resorbed upper jaw where sinus penetration is unavoidable. As implant displacement in the paranasal sinuses may be followed by infectious complications, an immediate or early removal of the displaced implants is indicated.